EU-compatible state measures and member states interests in public services - Horváth, Tamás (Central European Public Administration Review, 2018)
National interest, also as a critisism against the pradigm of New Public Management (NPM), is very much emphasised nowadays in public policies, even in sector ones. This article is about a removal from the classical meaning of general (public) interest to that new approach represented by certain EU Member States and the reasons behind. Our analysis focuses on contextual motives and impacts of these changes illustrated by the Hungarian case. The result shows that the market of public utility services has already been influenced by direct political considerations. Our findings indicate that these understandings for legitimate influence on EU market rules can also be derived from the legal framework itself. Measures examined in the paper run completely counter to the spirit of the original intention of the founders of the integration, and recent changes in EU law do not seem to raise unavoidable obstacles to such cases. Lessons of this case may be relevant for other EU Member States as well, at least for those from the Central-European region.
Keywords: centralizacija; javna uprava; javne storitve; Madžarska